Influence of Blended Learning on Outcomes of Students in a Rural Chemistry Class - S. Mandina (University of Sofia, 2019)
The merging of several teaching methods and pedagogic tools is a recurrent technique that is geared towards meeting the needs and expectations of students with varying dispositions, learning styles and intelligence styles. This study investigated the effects of blended learning on the outcomes of Ordinary Level students in a rural chemistry classroom in Zimbabwe. The study adopted a quasi-experimental research design with a non-equivalent control group. Purposive sampling technique was used to select two intact chemistry classes from two equivalent co-educational secondary schools that were distantly located from each other within rural schools in Gweru district. The main instrument used for the data collection was a Chemistry Achievement Test (CAT). The internal consistency of the instrument was obtained as 0.81 using the Test Retest method to establish the reliability. The researcher also administered survey questionnaire to students to solicit their views regarding blended learning and its implementation. Intact classes were used and in all, 67 students participated in the study (35 in the experimental group taught with the blended learning and 32 in the control group taught using the traditional method). Data collected for the study was analysed using ANCOVA. The obtained results indicated a statistically significant increase in the students' outcomes after being exposed to the blended learning approach. The findings showed positive perceptions of students on the blended learning environment. Recommendations were made that the blended learning strategy should be given more emphasis during teaching and learning of chemistry and be integrated into other related subjects in secondary schools.